Coral Reef Distribution in Raja Ampat: A Study of Marine Conservation Areas in West Papua - Souhoka, Jemmy; Cappenberg, H. A. W.; Susetiono; Nurjamin; Supriyadi, I. H.; Suyarso; Sidabutar, T. (Science and Technology - Recent Updates and Future Prospects Vol. 7, 2024)
This study investigates the distribution and diversity of hard coral reefs in the Raja Ampat Regency Marine Conservation Area (MCA) in West Papua, home to numerous islands and diverse marine species. The data was collected using the UPT (Underwater Photo Transect) method. The researchers identified 108 hard coral species from 49 genera and 15 families. In 2015, hard coral cover (HC) ranged from 18.60% to 49.33%, averaging 32.24%. In 2019, HC coverage varied between 17.80% and 68.93%, an average of 37.84%, an increase of 5.59% from 2015. The distribution of hard corals varied between 26 and 51 species per station, with the family Acroporidae being the most diverse, with 34 species. Eleven other families had 2–14 species, while Helioporidae, Milleporidae, and Dendrophyllidae were each represented by one species with a limited distribution. Species such as Montipora sp., Porites lobata, Porites nigrecens, and Porites sp. were widespread and were found at nine stations, while 39 species had a limited distribution. Bray-Curtis similarity matrix dendrogram analysis showed similar coral types between transect stations. The diversity of coral reefs increases the complexity and fertility of the surrounding waters. However, threats such as destructive fishing, coral mining, tourism, and climate change are impacting these ecosystems, leading to algae dominance and reduced living coral cover. Understanding these dynamics is critical to implementing conservation strategies to protect coral reefs and prevent overfishing.